A new approach to estimate the lead core characteristic strength of lead rubber bearings. (1st November 2022) - Pourmasoud, M.; Hajirasouliha, I.; Park, A.; Lim, J.B.P.
Highlights: The characteristics of lead rubber bearings are investigated using the results of 350 compression/tension shear tests. Lead yielding is variable and strongly influenced by the isolator configuration and the applied axial load. Despite current design equations, lead rubber bearings provide damping even under zero and tension load. A new design equation is proposed to estimate the lead core's yield strength by taking the influential factors into account. The proposed equation can estimate the yield strength of lead cores, on average, with less than 5% error. Abstract: The design of seismic isolators as specified by building code requirements is well defined and well established. However, there is still some refinement required for these design practices, especially in terms of estimating the yield strength and confinement of lead cores. The current codes have specified Upper Bound (UB) and Lower Bound (LB) criteria to encompass variability in the characteristic properties that determine the performance requirements of the isolators. The Lead Core is a key component in a Lead Rubber Bearing (LRB) that provides energy absorption resulting in the damping of a unit/system. Historically, designers have used a standard value for lead yield (8–10 MPa) depending on individual preferences. However, based on prototype test results, it has been shown that lead yielding is variable and strongly influenced by a number of physical parameters. This research aimed to develop a new approach for more accurate estimation of the yield strength of lead rubber bearings for practical design purposes. Over 350 compression-shear and tension-shear tests were carried out on 30 full-scale LRBs and the results were critically investigated. The results were then categorized based on confinement conditions, including high, medium, and low confinement, as defined further within this paper. The results illustrate that appropriate confinement provides a high yield strength level and ultimately an optimised seismic isolation design. The trend of yield strength index versus the stability index was developed and a new equation was proposed to calculate the lead core's yield strength as a function of the isolator configuration and the applied axial load.